Green Synthesis of Benevolent ZnO Nanorods Using Emblica officinalis - Gnanasangeetha, D.; Sarala Thambavani, D. (Asian Journal of Chemistry, 2015)
A proficient protocol for the production of zinc oxide nanorods without calcinations was developed by green synthesis method using aqueous leaf extract of Emblica officinalis. This green synthesis approach shows that the environmentally benign and renewable aqueous leaf extract of Emblica officinalis can be used as a stabilizing agent for the synthesis of zinc oxide nanorods. The process involved the use of zinc acetate dihydrate and sodium hydroxide as a antecedent and aqueous extract of Emblica officinalis as a solvent with assorted roles as promoter, stabilizer and template for synthesis of zinc oxide nanorod. The fashioned nanorod ranged in dimension of about 100-200 nm. Scanning electron microscope, energy dispersive X-ray analysis, X-ray diffraction and Fourier transform infrared spectroscopy entrenched that the formed nanorods are zinc oxide nanorods. The results showed that as-prepared ZnO nanorods had Wurtzite structure.